LEARNING FROM HOUSING: A Retrospective Narrative of Housing Environments in North Cyprus - Atun, Resmiye Alpar; Pulhan, Hifsiye (Open House Int, 2009)
This study attempts to assess housing developments on the island of Cyprus by referring to the various actions token and policies implemented during different periods as a result of changing socio-economic and political-dynamics. From this perspective, the methodology of the study is based on on assessment of housing developments throughout periods which coincide with certain socio-political thresholds in the history of the island, such as the year 7 974, which resulted in the division of the island into two as Northern and Southern ports, and the year 2004, in which the overall setting is changed as Southern port of the island become member of EU. The overall developments and transformations in housing developments ore considered as a mirror image of the actors, actions and associations in building activity throughout the periods referred to in this paper. Nicosia as the capital city of the island, has experienced different spatial transformations, and is comprised of a diversity of housing schemes ranging from the low cost housing units of urban workers, located next to the centers of traditional employment, to the large refugee housing estates and to the institutionalized social housing settlements. In this regard, the study aims to understand, interpret and learn from post experiences in the field of housing developments in order to provide lessons which will serve to support future sustainable living environments, since the current situation is at a critical point, and is currently requiring the interest and attention of the responsible authorities.
Keywords: Housing Environments; Social Housing; Cyprus; Socio-political Transformations; Sustainability